IPV and Health Consequences Among CPS-Involved Caregivers: A Fixed Effects Analysis Stratified by Race and Ethnicity - Termos, Mirvat (Violence against women, 2022)
Intimate partner violence (IPV) is a public health dilemma that disproportionately affects minority women in the United States. The present study utilized data from the National Survey of Child and Adolescent Well-Being (NSCAW II) to examine the longitudinal course of IPV outcomes reported by minority women involved with Child Protective Services (CPS). Our findings highlight the heterogeneity of the relationship between IPV and mental or physical health based on race/ethnicity. Nonetheless, additional research is necessary to investigate the impact of IPV severity on physical and mental health outcomes to ultimately facilitate race-specific interventions for women involved with CPS.